State of research of low-energy aluminum laser plasma - Livia Mesarosh; Месарош Лівіа; Mészáros Lívia (Europäische Wissenschaftsplattform, 2020)
Abstract. The paper presents results that improve the understanding of fundamental processes laser propagation of metals into the atmosphere of external gas at different pressure. It is established that at different intervals of the laser's existence plasma distribution is different, reflecting the corresponding change in temperature and electron concentration. Therefore, these results can be used for metal sputtering processes and to optimize chemical processes in the propagation of laser plasma of metals in gaseous atmospheres.
Keywords: aluminum laser plasma; plasma parameters; aluminum target